5u=-90

Simple and best practice solution for 5u=-90 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5u=-90 equation:



5u=-90
We move all terms to the left:
5u-(-90)=0
We add all the numbers together, and all the variables
5u+90=0
We move all terms containing u to the left, all other terms to the right
5u=-90
u=-90/5
u=-18

You can always share this solution

See similar equations:

| 3(15–2x)=7x+12–2x | | 9w=-90 | | 1.5h=5=2 | | q+-11=-63 | | 13x-118=6x-13 | | X+2÷3=x+34÷10 | | n=8=-4 | | x/24=30/15 | | -7+w=3 | | 16=-8(v+2) | | 45x+40=55 | | -5x+3(x+3)=-3 | | 1200/1000=x/14 | | 5h+10=-5 | | 11x+20x-6+5=-9x+5-6 | | 1000/1200=14/x | | 18w=36+9w | | -5+3(x+3)=-3 | | 1000/1200=14x | | 3(y-10)+1=0.75(y-8) | | n-8=-2n-2 | | a3-3=0 | | 11/21=b/24 | | 2y–59=y | | 6x^2+336=-90x | | (5x-3)+2=3.3 | | 20/12=30/t | | 3u–1=u+25 | | 6x-9=2+7) | | 9a-6=25 | | 18(x=1)=-54 | | 3e+4+e=13=e |

Equations solver categories